Effect of Gabapentin-Fluoxetine Derivative GBP1F in a Murine Model of Depression, Anxiety and Cognition - Gohar A; Ali G; Rashid U; Rauf K; Arif M; Khan MS; Alkahramaan YM; Sewell RDE (Dove Medical Press, 2023)
Aneela Gohar,1 Gowhar Ali,2 Umer Rashid,3 Khalid Rauf,1 Mehreen Arif,1 Muhammad Sona Khan,1 Yasser MSA Alkahramaan,1 Robert DE Sewell4 1Department of Pharmacy, COMSATS University Islamabad, Abbottabad Campus, Abbottabad, Pakistan; 2Department of Pharmacy, University of Peshawar, Peshawar, Pakistan; 3Department of Chemistry, COMSATS University Islamabad Abbottabad Campus, Abbottabad, Pakistan; 4Cardiff School of Pharmacy and Pharmaceutical Sciences, Cardiff University, Cardiff, UKCorrespondence: Khalid Rauf, Department of Pharmacy, COMSATS University Islamabad, Abbottabad Campus, Abbottabad, Khyber Pakhtoonkhwa, 22060, Pakistan, Email khalidrauf@cuiatd.edu.pkBackground and Objective: Gabapentin is a commonly prescribed antiepileptic agent for seizures, which is also used for pain and addiction management. Due to growing evidence of its abuse liability, there has been an incentive to synthesise potentially useful gabapentin derivatives devoid of adverse effects. A gabapentin adduct with a fluoxetine moiety, GBP1F, was assessed for any sedative, cognitive, anxiolytic, or antidepressant-like actions in murine behavioral models.Materials and Methods: Selected groups of mice were used for each behavioral paradigm, and the effect of GBP1F (5, 10, and 15 mg/kg) was assessed using spontaneous locomotor activity, the tail suspension test, elevated plus maze test, and the Y maze test models. Immediately following behavioral experiments, postmortem striatal and hippocampal tissues were evaluated for the effect of GBP1F on concentrations of dopamine, DOPAC, HVA, serotonin, 5-HIAA, vitamin C, and noradrenaline using high performance liquid chromatography with electrochemical detection.Results: GBP1F induced a mild suppression of locomotor activity, ameliorated anxiety and depression-like behavior, did not alter cognitive behavior, and raised serotonin and 5-HIAA concentrations in the hippocampus and striatum. GBP1F also positively enhanced dopamine and vitamin C tissue levels in the striatum. Thus, GBP1F represents a compound with anxiolytic- and antidepressant-like effects though further studies are warranted at the molecular level to focus on the precise mechanism(s) of action.Keywords: depression, anxiety, DOPAC, HVA, 5-HIAA, gabapentin, cognition